Pemberdayaan UMKM melalui Pemanfaatan QRIS sebagai Alat Pembayaran Digital di Kampung Cimasuk, Desa Suci - Afrina Farhaty Naufan; Akbar Rahman Hakim; Citra Aulia; Muhammad Hikmal; Syah Zehan Zakiyyatun Nafsiah; Utang Rosidin (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Purpose: The Community Service Program (KKN) carried out in Cimasuk Hamlet, Suci Village, was designed to implement the Quick Response Code Indonesian Standard (QRIS) as a digital payment mechanism aimed at enhancing the capacity of Micro, Small, and Medium Enterprises (MSMEs). The initiative was motivated by the persistence of cash-based transactions and the limited level of digital literacy within the local community. Method: Employing a qualitative descriptive approach with participatory engagement, this program positioned the community not merely as passive recipients of information but as active participants throughout the stages of introduction, socialization, and adoption of QRIS. The series of activities encompassed target mapping, stakeholder coordination, preparation of educational materials, dissemination, technical training, and continuous assistance. Practical Applications: The findings revealed a notable improvement in MSMEs’ knowledge and technical competence in utilizing QRIS, despite persisting challenges such as inadequate technological infrastructure and low financial literacy. Conclusion: Overall, the program contributed to strengthening MSME empowerment at the local level while simultaneously supporting national policies aimed at expanding digital financial inclusion and promoting sustainable economic development.